2015
DOI: 10.1002/jppr.1059
|View full text |Cite
|
Sign up to set email alerts
|

PRO‐OSTEO Extend I study (improving osteoporosis management in the acute and rehabilitation settings): multicentre audit

Abstract: Background Osteoporosis contributes to a large number of admissions to hospitals after minimal‐trauma fractures but is poorly recognised as an underlying cause of admissions and may be inadequately managed following hospitalisation. Aim The aim of this study was to examine osteoporosis management across Peninsula Health, assessing the effect of the introduction of a standard form to guide osteoporosis management after minimal‐trauma fractures. Method This was a retrospective cohort study measuring rates of ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…The PRO-OSTEO Extend 1 study has shown that the falls population treated at one of the Victorian Healthcare Services is similar to others [9] , and carries a significant medication-related burden in relation to medications that increase the risk of falls, with an average of more than 3 drugs per patient. This study has identified that PPI therapy was strongly associated with increased fracture rate, combined use with active osteoporosis treatment and a trend towards reduced treatment efficacy.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The PRO-OSTEO Extend 1 study has shown that the falls population treated at one of the Victorian Healthcare Services is similar to others [9] , and carries a significant medication-related burden in relation to medications that increase the risk of falls, with an average of more than 3 drugs per patient. This study has identified that PPI therapy was strongly associated with increased fracture rate, combined use with active osteoporosis treatment and a trend towards reduced treatment efficacy.…”
Section: Discussionmentioning
confidence: 86%
“…Over the two-year study period 560 patient admissions met the inclusion criteria and 305 admissions met the exclusion criteria for PRO-OSTEO Extend 1 study [9] . As part of this post-hoc analysis, 32 patients were excluded as the analysis examined adult population after minimal-trauma hospital admission.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite availability of evidence-based treatments, colecalciferol initiation rates of osteoporosis post minimal trauma fracture continue to be suboptimal. 11 This tertiary hospital audit site does not currently have a reliable process for the initiation of colecalciferol therapy post minimal trauma fracture, and anecdotal reports from clinical pharmacists suggest inconsistent practices for initiation between hospital units. Many patients are referred to their general practitioner for follow-up, and some patients receive no instructions.…”
Section: Introductionmentioning
confidence: 97%